Isolation of a [Fe(CO)4]2–Bridged Diuranium Complex Obtained via Reduction of Fe(CO)5with Uranium(III) - Ward, Robert J.; Pividori, Daniel Maximilian; Carpentier, Ambre; Tarlton, Michael L.; Kelley, Steven P.; Maron, Laurent; Meyer, Karsten; Walensky, Justin R. (Organometallics, 2021)
Treatment of the U(III) complex, [(C5Me5)2U(OMes)(THF)], Mes = 2,4,6-Me3C6H2, with Fe(CO)5 forms [(C5Me5)2(MesO)U2(μ2-(OC)2Fe(CO)2)] with the bridging, tetrahedral Fe(CO)4 moiety. This complex has been studied using 1H NMR, IR vibrational, UV-vis electronic absorption, and zero-field 57Fe Mössbauer spectroscopy as well as single-crystal X-ray diffraction analysis, magnetic measurements, and DFT calculations.
CRIS-Team Scopus Importer:2021-06-04